Selective S-methylation of highly fluorinated thiocarbamates. Issue 1 (2nd January 2017) - Chniti, Ines; Maouati, H.; Sanhoury, M. A. K.; Merlet, D.; Chehidi, I.
ABSTRACT: A series of new S -methyl O -fluoroalkyl N -alkyl(aryl)imidothiocarbonates were prepared by S -methylation of various fluoroalkylated thiocarbamates with methyl iodide in the presence of cesium carbonate and tetrabutylammonium iodide (TBAI) in tetrahydrofuran (THF) at room temperature. As expected from the mostly soft electrophilic alkyl halide (MeI), no isomer products derived from N -methylation were detected. The products were characterized by spectroscopic ( 1 H, 13 C and 19 F) NMR, infrared, and high-resolution mass spectrometric techniques. GRAPHICAL ABSTRACT: